Adaptive responses of cell hydration to a low temperature arrest. (22nd December 2015) - Christmann, Jens; Azer, Lale; Dörr, Daniel; Fuhr, Günter R.; Bastiaens, Philippe I. H.; Wehner, Frank
Abstract : Key points: Na + conducting cation channels are key players in the volume restoration of osmotically shrunken cells. Accordingly, they are potential candidates for the compensation of water loss during slow‐freezing procedures. Cells were subjected to different levels of hypertonic stress, aiming to disturb cell water content and to define the energy demands of water channels and Na + channels in the process of rehydration. Activation of Na + channels was clearly the rate‐limiting step in the restoration of cell volume post‐cryo, whereas water channels merely played a permissive role. Low temperatures increased cell viscosity with a remarkable hysteresis; furthermore, increasing cell viscosity experimentally was shown to stimulate Na + channels. The peptide hormone vasopressin was a further activator of Na + channels and increased the viability of post‐cryo cells considerably. This opens the path for a new class of cryo‐protectants with an intrinsic biological activity. Abstract: Slow cooling leads to a passive dehydration of cells, whereas rehydration during warming reflects the active regain of functionality. The ability to modulate such an energy demanding process could be instrumental in optimizing the cryo‐arrest of living systems. In the present study, various levels of hypertonic stress were used to disturb the water content of cells and to define the energy profiles of aquaporins and (Na + conducting) cation channels during rehydration. Na + import was found to be the rate‐limiting step in water restoration, whereas aquaporins merely played a permissive role. Indeed, regulated Na + import was increased 2‐fold following cryo‐arrests, thus facilitating the osmotic rehydration of cells. Freezing temperatures increased cell viscosity with a remarkable hysteresis and viscosity was a trigger of cation channels. The peptide hormone vasopressin was a further activator of channels, increasing the viability of post‐cryo cells considerably. Hence, the hormone opens the path for a novel class of cryo‐protectants with an intrinsic biological activity. Key points: Na + conducting cation channels are key players in the volume restoration of osmotically shrunken cells. Accordingly, they are potential candidates for the compensation of water loss during slow‐freezing procedures. Cells were subjected to different levels of hypertonic stress, aiming to disturb cell water content and to define the energy demands of water channels and Na + channels in the process of rehydration. Activation of Na + channels was clearly the rate‐limiting step in the restoration of cell volume post‐cryo, whereas water channels merely played a permissive role. Low temperatures increased cell viscosity with a remarkable hysteresis; furthermore, increasing cell viscosity experimentally was shown to stimulate Na + channels. The peptide hormone vasopressin was a further activator of Na + channels and increased the viability of post‐cryo cells considerably. This opens the path for a new class of cryo‐protectants with an intrinsic biological activity.